INFORMATION TECHNOLOGY AUDIT USING COBIT 5 ON DELIVER DOMAIN, SERVICE AND SUPPORT (DSS) IN PT. XYZ, A MINING COMPANY - Joe Yuan Mambu; Valentshea Doringin; Sintya Hamise; Erienika M Lompoliu (Informatics Engineering Department of Halu Oleo University, 2020)
Information Technology (IT) is crucial for companies. With technology, all jobs can be made easily by humans and can advance business processes more quickly and effectively. To find out the extent of the company's development in IT processing, an audit is needed. Without an efficient use of IT, companies will only waste IT-related investment that has been made. The purpose of this study is to audit IT governance implemented in a mining company XYZ. The IT governance audit that we use is based on the COBIT 5. framework. In this study, we use one Deliver, Service, Support (DSS) domain that includes six subdomains: DSS01 (Manage Operations), DSS02 (Manage Service requests and Incidents), DSS03 (Manage Problems), DSS04 (Manage Continuity), DSS05 (Manage Security Service), and DSS06 (Manage Business Process Control). For data collection in this study, researchers used interviews and questionnaire methods for related parties. The results of the IT Maturity Level for DSS domains reached an average level 2 or Managed Process, which shows that the company was able to operate the IT process yet with unclear definition and standard operating procedure nor evaluation or planned improvement.Keywords; COBIT 5, DSS, Capability Level, IT Auditing